Openness to change: experiential and demographic components of change in in Local Health Department leaders - Emmanuel D Jadhav; James W. Holsinger; David W Fardo (Frontiers Media S.A., 2015)
Background: During the 2008-10 economic recession, Kentucky local health department (LHD) leaders utilized innovative strategies to maintain their programs. A characteristic of innovative strategy is leader openness to change. Leader demographical research in for-profit organizations has yielded valuable insight into leader openness to change. For LHD leaders the nature of the association between leader demographic and organizational characteristics on leader openness to change is unknown. The objectives of this study are to identify variation in openness to change by leaders' demographic and organizational characteristics and to characterize the underlying relationships. Material and Methods: The study utilized Spearman rank correlations test to determine relationships between leader openness to change (ACQ) and leader and LHD characteristics. To identify differences in the distribution of ACQ scores, Wilcoxon-Mann-Whitney and Kruskal Wallis non-parametric tests were used, and to adjust for potential confounding linear regression analysis was performed.Data: LHD leaders in the Commonwealth of Kentucky were the unit of analysis. Expenditure and revenue data were available from the state health department. National census data was utilized for county level population estimates. A cross-sectional survey was performed of KY LHD leaders' observable attributes relating to age, gender, race, educational background, leadership experience and openness to change. Results: Leaders had relatively high openness to change scores. Spearman correlations between leader ACQ and departmental 2012-13 revenue and expenditures were statistically significant, as were the differences observed in ACQ by gender and the educational level of the leader. Differences in ACQ score by education level and agency revenue were significant even after adjusting for potential confounders. The analyses imply there are underlying relationships between leader and LHD characteristics based on leader ACQ.